2019
DOI: 10.1177/0892705719872524
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical properties of polyamide 6/polystyrene (PA6/PS) reinforced by PbO2 composites for X-ray shielding

Abstract: Thermal, electrical, as well as mechanical behavior of blends of polyamide 6/polystyrene (PA6/PS) (50/50 wt/wt%) loaded with different concentrations of lead dioxide (PbO2) were investigated for X-ray shielding. Thermal stability and hardness (shore D) of these composites are studied. Addition of PbO2 decreases the thermal stability of the prepared composites. Stability of thermal properties confirmed by determining the activation energy for the thermal decomposition of unfilled PA6/PS and filled composites ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…It was observed that the additions of conductive materials to these polymers not only increases the electrical conductivity but also improves its mechanical properties. [7][8][9][10][11][12] Rubber is comprehensively utilized in various fields of modern and cultural applications because of its excellent elasticity and reversible deformability, just as water and heat resistance properties. On the off chance that NR is proposed to satisfy market consumptions, its undesired actual properties should be improved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the additions of conductive materials to these polymers not only increases the electrical conductivity but also improves its mechanical properties. [7][8][9][10][11][12] Rubber is comprehensively utilized in various fields of modern and cultural applications because of its excellent elasticity and reversible deformability, just as water and heat resistance properties. On the off chance that NR is proposed to satisfy market consumptions, its undesired actual properties should be improved.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the additions of conductive materials to these polymers not only increases the electrical conductivity but also improves its mechanical properties. 7-12…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray spec tra are a com bi na tion of nar row peaks on a con tin u ous spec trum, formed as a re sult of char ac ter is tics and brems strah lung ra di a tion. The major ity of di ag nos tic X-ray en er gies are in the range of 25 keV to around 200 keV [1]. The en ergy spec trum of the X-ray beam is crit i cal in both di ag nos tics and ther a peutics for the cor rec tion of beam hard en ing ar ti facts, the pre dic tion of im age qual ity, and the eval u a tion of de tector per for mance [2].…”
Section: Introductionmentioning
confidence: 99%
“…Polyamide 6 (PA6) is well known as high performance engineering plastic with high strength, good fatigue resistance, and satisfactory wearing durability [ 1 , 2 , 3 , 4 ]. However, its poor notched impact toughness (especially at low temperatures) restricts its overall performance, which limits its applications in modern plastic industries and newly emerging fields [ 5 , 6 , 7 , 8 , 9 ], e.g., wearable fabrics [ 4 ], self-supporting water purification films [ 9 ], and nanofiltration membrane [ 7 ], etc.…”
Section: Introductionmentioning
confidence: 99%